2017
DOI: 10.17063/bjfs6(4)y2017599
|View full text |Cite
|
Sign up to set email alerts
|

Estudo Retrospectivo da Destinação de Aves Silvestres Apreendidas pela Polícia Militar Ambiental do Estado de São Paulo no Período de 2012 a 2015

Abstract: A grande variedade e a exuberância da avifauna brasileira tornam o país muito atrativo para aqueles que querem lucrar com o comércio ilegal de animais silvestres. O combate a tais crimes exige uma ação ordenada e eficaz por parte dos órgãos de segurança pública, com consequente identificação dos infratores e apreensão dos animais envolvidos. Entretanto, a apreensão não é medida que se esgota em si, pois implica em procedimentos visando a adequada destinação dos animais. O problema da destinação de fauna apreen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
4
0
1
Order By: Relevance
“…Araujo et al, 2010;Gogliath et al, 2010;de Moura et al, 2012;Nunes et al, 2012). Five studies analyzed data from PAm facilities (Preuss and Schaedler, 2012;Viana and Zocche, 2013;de Medeiros, 2014;Reis et al, 2017;Pinto, 2018), with only two looking at data from CRAS (de Brito, 2017; Neto, 2018; Supplementary Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Araujo et al, 2010;Gogliath et al, 2010;de Moura et al, 2012;Nunes et al, 2012). Five studies analyzed data from PAm facilities (Preuss and Schaedler, 2012;Viana and Zocche, 2013;de Medeiros, 2014;Reis et al, 2017;Pinto, 2018), with only two looking at data from CRAS (de Brito, 2017; Neto, 2018; Supplementary Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Localities that were surveyed more than once were done so in different time periods; e.g., the same CETAS in the MG State was surveyed in 2008 (Freitas et al, 2015) and 2011 (de Oliveira Souza et al, 2014). Some municipalities were surveyed more than once, but done so in different localities; e.g., the municipality of São Paulo had the CETAS of Animália and Depave surveyed from 2003 to 2008 (Morita, 2009), while its Environmental Police Center was surveyed from 2012 to 2015 (Reis et al, 2017). In total, we compiled information for 20 localities (Figure 2).…”
Section: Methodsmentioning
confidence: 99%
“…In this list of trafficked animals are birds, which have a high number of captures. In view of this, Reis et al (2017) claim that Brazil has become one of the main routes of wild bird traffickers since the Brazilian avifauna is highly coveted due to its exuberance and the great variety of existing species. This, according to Velden (2018), generates, annually, a financial flow on the order of 2,500 million reais, and 12 million animals extracted from their natural habitats.…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, it is important to understand the extent of the trafficking of these animals by collecting accurate data so that combating measures can be implemented to curb this illegal business, and environmental awareness campaigns and more severe punitive laws can be developed (Pyke and Szabo, 2018). Several research studies have been conducted on wild bird trafficking, such as the ones carried out by Hidasi et al (2013), Menes and Simonian (2016), Reis et al (2017), Restrepo-Rodas and Pulgarín-Restrepo (2017), Cavalcanti and Nunes (2019), Ferreira and Barros (2020), Pontes Filho et al (2021), Sales et al (2022), and. All these studies have shown that bird trafficking is growing all over the world, especially in countries with great biodiversity such as Brazil, and that it is difficult to eradicate since the traffickers are increasingly equipped, use routes, and lure uneducated people lacking environmental education, who live in poverty and need to survive, and thus are attracted by the low values offered.…”
Section: Introductionmentioning
confidence: 99%
“…Tanto em aves de vida livre quanto nas provenientes de tráfico, Sanches (2008), relaciona as causas de mortalidade distribuindo da seguinte forma: processos infecciosos, predominantes entre os animais de tráfico, caracterizados principalmente por infecções mistas por agentes bacterianos, fúngicos e virais, enquanto os processos não infecciosos, estão associadas as lesões traumáticas. Segundo Reis et al (2017) estas alterações a contenção em gaiolas inapropriadas quanto ao espaço e/ou quanto ao número de aves distribuídas nestas.…”
Section: Introductionunclassified